2014
DOI: 10.1007/s00259-014-2909-1
|View full text |Cite
|
Sign up to set email alerts
|

MIBG scans in patients with stage 4 neuroblastoma reveal two metastatic patterns, one is associated with MYCN amplification and in MYCN-amplified tumours correlates with a better prognosis

Abstract: PurposeThe aim of this study was to find clinically relevant MIBG-avid metastatic patterns in patients with newly diagnosed stage 4 neuroblastoma.MethodsDiagnostic 123I-MIBG scans from 249 patients (123 from a European and 126 from the COG cohort) were assessed for metastatic spread in 14 body segments and the form of the lesions: “focal” (clear margins distinguishable from adjacent background) or “diffuse” (indistinct margins, dispersed throughout the body segment). The total numbers of diffuse and focal lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Another group has previously reported that, among MIBG avid tumors, MYCN status is not associated with intensity of MIBG uptake . However, MYCN‐ amplified tumors have been reported to lead to more focal uptake on MIBG scans, which may have increased the potential for false negative interpretation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group has previously reported that, among MIBG avid tumors, MYCN status is not associated with intensity of MIBG uptake . However, MYCN‐ amplified tumors have been reported to lead to more focal uptake on MIBG scans, which may have increased the potential for false negative interpretation …”
Section: Discussionmentioning
confidence: 99%
“…19 However, MYCN-amplified tumors have been reported to lead to more focal uptake on MIBG scans, which may have increased the potential for false negative interpretation. 20 We were able to leverage data from the TARGET initiative to determine whether expression of key genes of interest differ between MIBG avid and nonavid tumors. We demonstrated that NET mRNA expression, but not VMAT2 mRNA expression, is lower in MIBG nonavid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Though several potential biologic markers for substratification of risk in stage M neuroblastoma have been identified, their precise relationship to disease progression remains unclear . Patterns of metastasis may provide insight into biologic mechanisms of disease progression and provide a basis for imaging‐based risk stratification in high‐risk, stage M neuroblastoma …”
Section: Discussionmentioning
confidence: 99%
“…[4,18,19] Patterns of metastasis may provide insight into biologic mechanisms of disease progression and provide a basis for imaging-based risk stratification in high-risk, stage M neuroblastoma. [10,20,21] Bone metastasis is associated with poor prognosis in neuroblastoma and is present in most children with stage M disease. [2,3,10] In this study, we found that while extraorbital bone metastasis conferred no additional risk in children ࣙ18 months of age with stage M (high-risk) disease, the presence of orbital bone metastasis was associated with decreased overall and 5YS postdiagnosis of neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…1 The pattern and extent of metastatic disease (number of systems/compartments involved) is also prognostic in patients with high-risk metastatic disease. [3][4][5] The presence of tumour segmental chromosomal abnormalities (SCA) 6 and pattern of metaiodobenzylguanidine (mIBG) uptake (particularly in patients with MNA tumours) 7 also have prognostic impact. The extent of mIBG-avid disease (assessed using semi-quantitative scoring) at diagnosis and after induction chemotherapy correlates with outcome.…”
Section: Introductionmentioning
confidence: 99%